Determinants of Demand for Higher Education in Indonesia: Evidence from Indonesia Family Life Survey - Rifa'i, Achmad; Irwandi, Irwandi; Mendy, David (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2019)
The most outstanding event in recent history has been the continuous increase in the proportion of students entering higher education. Thus, it seems reasonable to assume to what extent this significant increase in higher education participation has a connection to the individual characteristics, social-economic, religion, gender ethnicity geography variables. Using data from the IFLS, a binomial logit model was fitted to determine the factors that influence an individual to pursue a higher-level education as observed by the recent rise in the demand for higher education in Indonesia. The empirical findings of the study indicate the following: firstly, individual characteristic; score, school type are relevant variables for individual participation in higher education. Secondly, for the socioeconomic variables; income, father?s education, mother?s education, household status, household size are important variables for individual participation in higher education. Finally, for the gender, ethnicity variables; the results were quite shocking, both Javanese and Male are the less likely to demand higher education in Indonesia. Further, regional and geographic variables were found to be insignificant.